Analisis Faktor-faktor yang Mempengaruhi Adopsi Teknologi 5G di Kota Bandung - Alhafizh, Dzaki; Tritoasmoro, Iwan Iwut; Nur, Levy Olivia (Jurnal Teknologi Informasi dan Pendidikan, 2025)
This research aims to examine determinants influencing the adoption of 5G technology among users in Bandung City. As Indonesia begins its transition toward advanced communication infrastructure, understanding user behavior and adoption level becomes important, especially in Bandung city. Use a quantitative approach, this research collected data from 206 respondents through a structured questionnaire designed to capture various technical and non-technical factors. Eight independent variables were analyzed infrastructure availability, technology awareness and knowledge, network service quality, service and device cost, perception of security and privacy, potential and benefits offered by 5G, user experience, and social influence. Data analysis was performed using ordinal logistic regression to determine which factor adopted 5G technology. The results reveal that network service quality, perception of security and privacy, and social influence have a statistically significant negative effect on adoption levels. Meanwhile, the remaining variables showed no significant influence. Based on the research findings, the article provides recommendations such as improving network service quality, optimizing security and privacy, and increasing public awareness campaigns to address user concerns and support broader adoption of 5G technology. These efforts are expected to enhance user experience and accelerate the implementation of 5G in support of smart city development in Bandung.